1981
DOI: 10.1016/s0006-3495(81)84870-9
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance transverse relaxation in muscle water

Abstract: The origin of the nonexponentiality of proton spin echoes of skeletal muscle has been carefully examined. It is shown that the slowly decaying part of the proton spin echoes is not due to extracellular water. First, for muscle from mice with in vivo deuteration, the deuteron spin echoes were also nonexponential, but the slowly decaying part had a larger weighing factor. Second, for glycerinated muscle in which cell membranes were disrupted, the proton spin echoes were similar to those in intact muscle. Third, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 32 publications
1
50
0
Order By: Relevance
“…Fung and Puon (12) found that R 2 varies directly with pH i in chemically skinned rabbit psoas muscle fibers. Moser et al (13) also observed a direct linear relationship between R 2 and pH i in isolated rat liver throughout the range of ϳ6.2 to ϳ6.8 pH units.…”
Section: The R 2i Decrease Is Partly Due To Increased Intracellular Vmentioning
confidence: 98%
See 1 more Smart Citation
“…Fung and Puon (12) found that R 2 varies directly with pH i in chemically skinned rabbit psoas muscle fibers. Moser et al (13) also observed a direct linear relationship between R 2 and pH i in isolated rat liver throughout the range of ϳ6.2 to ϳ6.8 pH units.…”
Section: The R 2i Decrease Is Partly Due To Increased Intracellular Vmentioning
confidence: 98%
“…T 2 is inversely related to intracellular pH (pH i ) in chemically-skinned rabbit psoas muscle (12) and in isolated rat liver (13). End-exercise pH i and T 2 are also correlated (2,14); however, during incremental arm ergometer exercise, pH i changes lag T 2 changes, and during recovery from this exercise, pH i recovers more quickly than T 2 (15).…”
mentioning
confidence: 99%
“…In addition to alterations in the size, shape, and charge of surfaces in muscle cells, contraction involves the production and/or translocation of ions and metabolites. These processes would have osmotic effects that alter the concentration of water as well as direct effects on the MR relaxation of water; e.g., T 2 was shown to increase as pH was lowered (12).…”
Section: Rmmentioning
confidence: 99%
“…Proposed explanations for intracellular T2 increases include the accumulation of end products of cellular energy metabolism, which cause water to move into the cell (4,21), decreased intracellular pH (4,8), and water shifts from an intracellular compartment possessing a short T2 (ϳ20 ms) to a second intracellular compartment having a longer T2 (ϳ40 ms) (22,23). Any of these possible explanations, acting alone or in concert with the others, suggests that the intracellular T2 increase results from changes in the chemical behavior of water resulting from increased flux through energy metabolism pathways.…”
mentioning
confidence: 99%